Analysis of the Main Factors Influencing the Dominant Frequency of Blast Vibration - Da Liu; Wenbo Lu; Yijia Liu; Ming Chen; Peng Yan; Pengchang Sun (Shock and Vibration)
At present, the study on the dominant frequency of blasting vibration is still a worldwide problem. Compared with the mature research on the particle peak velocity of blasting vibration, the researches on the dominant frequency of blasting vibration are much less. In this paper, by analyzing the main influencing factors of the dominant frequency, an attenuation equation of the dominant frequency induced by blasting vibration has been proposed by dimensional analysis combined with the theory of radial spherical wave propagation. The proposed equation is applied to the fitting analysis on the dominant frequency measured in Zhoushan Green Petrochemical Base in China, which has obtained a favorable fitting correlation. Based on the fitting analysis, it has found that the correlation coefficient of radial vibration obtained by the proposed equation is higher than that of vertical vibration, which is resulted from the reason that the vibration in vertical is considered to be influenced most by the R-wave on the ground and perceived to be quite different from the radial vibration affected by P-wave. In generally, different components of blasting waves will affect the attenuation of dominant frequency.